Research on Discontinuous Contact Intra-strand Steel Stress of Steel Rope Ring CVT - Wu Zhang; Weixiong Liu; Lü Changlei; Feiyan Han (Jixie chuandong)
In order to explore the stress distribution of steel wire in the strand when the curved steel rope is in contact with continuous and discontinuous grooves， taking the 6×19+IWS right cross-twisted steel rope as the research object， the finite element models of contact between steel ropes and continuous and discontinuous grooves are established respectively， and the stress distribution of the steel wire in continuous and discontinuous contact is analyzed. The results show that under the condition of continuous and discontinuous contact， the equivalent stress value of the outer steel rope in contact with the rope groove is the largest， followed by the steel rope at the contact between the strand and the strand， and the equivalent force value of the steel rope at other positions is the smallest under the same axial load. The change range of equivalent stress produced by steel rope in discontinuous contact is higher than that in continuous contact. The surface contact stress of discontinuous rope grooves is 39.5% larger than that of continuous rope grooves， and the maximum contact stress of surface steel rope in discontinuous contact is 5.08% higher than that in continuous contact. The wear test of steel rope under continuous and discontinuous contact shows that the average length and width of steel rope wear scar in discontinuous contact are 25.5% and 13.5% higher than those in continuous contact， respectively， which are consistent with the simulation results.